Smut fungi (Ustilaginomycetes and Microbotryales, Basidiomycota) in Panama - Piepenbring, Meike (Revista de Biología Tropical, 2001)
This is the first publication dedicated to the diversity of smut fungi in Panama based on field work, the study of herbarium specimens, and references taken from literature. It includes smuts parasitizing cultivated and wild plants. The latter are mostly found in rural vegetation. Among the 24 species cited here, 14 species are recorded for the first time for Panama. One of them, Sporisorium ovarium, is observed for the first time in Central America. Entyloma spilanthis is found on the host species Acmella papposa var. macrophylla (Asteraceae) for the first time. Entyloma costaricense and Entyloma ecuadorense are considered synonyms of Entyloma compositarum and Entyloma spilanthis respectively. For the new conbination Sponsorium panamensis see note at the end of this publication. Descriptions of the species are complemented by some illustrations, a checklist, and a key.